L' histoire du mouvement makhnoviste (1918-1921) - Voline; Archinov, Piotr (Paris : Les Editions Anarchistes, 1921)
Fonds Perrone
Frans
Monografie
Keywords: Makhno, Nestor Ivanovich; anarchisme; Oktoberrevolutie; Sovjet-Unie.; Oekraïne